PLASMA BRAIN-DERIVED NEUROTROPHIC FACTOR LEVELS OF PATIENTS UNDERGOING HEMODIALYSIS AND PERITONEAL DIALYSIS - Seok Joon Shin (Kidney Research and Clinical Practice, 2012)
Recent studies have shown that brain-derived neurotrophic factor (BDNF) is associated with neurotoxic, inflammatory and nutritional status. The purpose of this study is to investigate the changes in plasma BDNF concentration that were induced by chronic uremic condition. Using an enzyme-linked immunosorbent assay (ELISA), we measured peripheral BDNF levels in pre-hemodialysis (pre-HD), peritoneal dialysis (PD) patients and in a control group. The plasma BDNF concentrations of pre-HD, PD patients were significantly higher compared with those of controls (856.3±879.1, 1167.9±647.5 versus 403.1±288.9 pg/ml, respectively). The plasma BDNF in dialysis patients was positively correlated with high-sensitivity C reactive protein (hs-CRP) and with serum albumin negatively. Plasma BDNF hs-CRP Albumin